Preoperative Nutritional Therapy Reduces the Risk of Anastomotic Leakage in Patients with Crohn’s Disease Requiring Resections - Zhen Guo; Dong Guo; Jianfeng Gong; Weiming Zhu; Lugen Zuo; Jing Sun; Ning Li; Jieshou Li (Gastroenterology Research and Practice)
Background. The rate of anastomotic leakage is high in surgeries for Crohn’s disease, and therefore a temporary diverting stoma is often needed. We conducted this study to investigate whether preoperative nutritional therapy could reduce the risk of anastomotic leakage while decreasing the frequency of temporary stoma formation. Methods. This was a retrospective study. Patients requiring bowel resections due to Crohn’s disease were reviewed. The rate of anastomotic leakage and temporary diverting stoma was compared between patients who received preoperative nutritional therapy and those on a normal diet before surgery. Possible predictive factors for anastomotic leakage were also analyzed. Results. One hundred and fourteen patients undergoing 123 surgeries were included. Patients in nutritional therapy (NT) group had a significantly lower level of C-reactive protein on the day before surgery. Patients in NT group suffered less anastomotic leakage (2.3% versus 17.9%, P=0.023) and less temporary diverting stoma (22.8% versus 40.9%, P=0.036). Serum albumin of the day before surgery ≤35 g/L and preoperative nutritional therapy were identified as factors which independently affected the rate of anastomotic leakage. Conclusion. Preoperative nutritional therapy reduced the risk of anastomotic leakage and the frequency of temporary diverting stoma formation in patients with Crohn’s disease requiring resections.